2007
DOI: 10.3844/ajassp.2007.619.627
|View full text |Cite
|
Sign up to set email alerts
|

Potential Air and Groundwater Pollution from Continuous High Land Application of Cheese Whey

Abstract: Experiments were performed, using eighteen 280 cm deep soil columns with 20 cm inside diameter, to determine the relative amounts of nitrogenous compounds leached and volatilized from soils receiving high application rates of cheese whey during two seasons. Three soils (loamy sand, sandy loam and sandy clay loam) and two cheese whey application rates (560 and 840 kg-N ha¯1), that provided twice and three times the nitrogen requirement for corn crop, were investigated. The leaching and volatilization processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…A cheese processor provided an average of 46% of total influent to the WWTP. Thus, N and P additions from cheese whey solids (Ghaly et al, 2007;Wendorff and Matzke, 1993) and alkaline cleaning agents common in dairy processing (Britz et al, 2006) likely made important contributions to effluent TKN, P, and alkalinity ( Table 1). The BOD and COD concentrations (Table 1) were low for cheese processing plants (Britz et al, 2006), which may have resulted from dilution by the other tenants.…”
Section: Effluent Chemical Analysis and Plot Irrigationmentioning
confidence: 96%
“…A cheese processor provided an average of 46% of total influent to the WWTP. Thus, N and P additions from cheese whey solids (Ghaly et al, 2007;Wendorff and Matzke, 1993) and alkaline cleaning agents common in dairy processing (Britz et al, 2006) likely made important contributions to effluent TKN, P, and alkalinity ( Table 1). The BOD and COD concentrations (Table 1) were low for cheese processing plants (Britz et al, 2006), which may have resulted from dilution by the other tenants.…”
Section: Effluent Chemical Analysis and Plot Irrigationmentioning
confidence: 96%
“…Pesticides are among the major organic compounds that are discharged into the water resources in Middle Eastern countries, which has raised a primary public concern in the recent years [1,2]. These compounds are classified by the Agency of Toxic Substances & Disease Registry (ATSDR), USA as a group in the top priority list of chemicals that need urgent control [3].…”
Section: Introductionmentioning
confidence: 99%
“…The major component of whey is lactose (5–7%), plus lesser amounts of glucose and galactose, proteins (0.8–1.2%), and lipids (0.06–3%) . Whey final disposal is a central problem for the dairy industry due to their high values ​​of chemical oxygen demand (COD) (50,000 to 70,000 g/L), which generates significant pollution when wastes are freely disposed in the environment , and the high costs of their eventual treatment. The bioconversion of whey to valuable microbial oils is an interesting avenue, which may allow reducing the environmental impact caused by the disposal of this waste in natural environments, and simultaneously generating at low cost, lipids useful for the production of biodiesel, bio‐lubricants, oleochemicals, cosmetics, among other bioproducts.…”
Section: Introductionmentioning
confidence: 99%
“…The genetics of lactose and galactose utilization in actinobacteria is still incipient, and remains to be elucidated in detail. Previous studies have suggested that a solute binding protein dependent transport system (SBPT) may be responsible for the transport of lactose and galactosides in Streptomyces coelicolor A3(2) and in Rhodococcus opacus (PD630 and B4) , which is clustered with a probable β‐galactosidase involved in lactose degradation.…”
Section: Introductionmentioning
confidence: 99%